2016
DOI: 10.1186/s12864-016-3004-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacillus anthracis CodY regulation under host-specific environmental factor deprived conditions

Abstract: BackgroundHost-specific environmental factors induce changes in Bacillus anthracis gene transcription during infection. A global transcription regulator, CodY, plays a pivotal role in regulating central metabolism, biosynthesis, and virulence in B. anthracis. In this study, we utilized RNA-sequencing to assess changes in the transcriptional patterns of CodY-regulated B. anthracis genes in response to three conditions of environmental starvation: iron, CO2, or glucose deprivation. In addition, we performed chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…As a global negative regulator, CodY is usually a transcriptional repressor of its target genes, which binds to the promoter of these genes or directly to genes to block the binding of RNA polymerase (Kim, Jung, & Chai, 2016). From Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a global negative regulator, CodY is usually a transcriptional repressor of its target genes, which binds to the promoter of these genes or directly to genes to block the binding of RNA polymerase (Kim, Jung, & Chai, 2016). From Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is not surprising that the bacterial community composition was more closely related (higher correlation coefficient) with functional gene abundance than with soil enzyme activity. Although functional genes are inherent to bacterial taxa, their transcription and translation are greatly regulated by environmental conditions (Schreiber et al, 2007; Kim et al, 2016; Hockenberry et al, 2017). Taking nitrate respiration as example, a serial of functional genes ( nar , nir ) are regulated by anaerobic condition and nitrate presence via transcription network in Pseudomonas aeruginosa (Schreiber et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These include a 2.39‐fold increase in early macrophage infections and a ~ twofold increase when either of the thiol‐stress response regulators Spx1A or Spx2A were overexpressed (Dixon et al , ; Bergman et al , ). The largest change we found was again from the Kim et al study where hmoB was downregulated 6.6‐fold in Δ codY strains in aeriated Ristroph media lacking bicarbonate/CO 2 (Kim et al , ). The increase transcription observed in macrophages does correlate with our observation that loss of this gene makes bacilli more susceptible to macrophage‐based killing.…”
Section: Discussionmentioning
confidence: 67%
“…Activation of hmoA by Spx, which is in turn repressed by PerR, would fit with the model proposed by Chandrangsu and Helmann in B. subtilis . Both IsdG and HmoA appear to be regulated by the global virulence regulator CodY, which is not surprising considering CodY has been implicated in heme iron acquisition before (Château et al , ; Kim et al , ). In studies done by Kim et al neither hmoA nor isdG showed increased expression under iron‐starved conditions unless codY was deleted (Kim et al , ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation